2017
DOI: 10.3389/fnbeh.2017.00099
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Sertraline Intake Reverses the Behavioral Changes Induced by Prenatal Stress in Rats in a Sex-Dependent Way

Abstract: Early life stress is a major factor underlying the vulnerability to respond to stressful events later in life. The present study attempted to evaluate the role of prenatal stress affecting the development of stress-related disorders and their reversion by postnatal exposure to Sertraline (SERT), a front-line medication for medication for posttraumatic stress disorder (PTSD) in humans. To achieve this, adult male and female prenatally stressed (PS) or unstressed (Controls) offspring rats, following oral chronic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 53 publications
(128 reference statements)
0
10
0
1
Order By: Relevance
“…While footshock pain thresholds are not influenced by sex in C57Bl/6 mice (Podhorna, McCabe, & Brown, ), female rodents, compared to males, are considered more vulnerable to acute stressors (Kokras & Dalla, ). Thus, studies have revealed that the prevalence of jumping is highest among female rodents (Day et al, ; Pereira‐Figueiredo et al, ). In the current study, jumping was exhibited infrequently by males and females across all fear inhibition models tested.…”
Section: Discussionmentioning
confidence: 99%
“…While footshock pain thresholds are not influenced by sex in C57Bl/6 mice (Podhorna, McCabe, & Brown, ), female rodents, compared to males, are considered more vulnerable to acute stressors (Kokras & Dalla, ). Thus, studies have revealed that the prevalence of jumping is highest among female rodents (Day et al, ; Pereira‐Figueiredo et al, ). In the current study, jumping was exhibited infrequently by males and females across all fear inhibition models tested.…”
Section: Discussionmentioning
confidence: 99%
“…Modifications of the PPI are very diverse and may be caused by neurological [ 59 ] or psychiatric diseases characterized by anxiety symptoms [ 60 , 61 ], behavioral states (such as emotional context or a stressor) [ 62 , 63 , 64 ], hormonal levels [ 37 , 65 , 66 ], and even adaptations derived from particularities of some professions, as occurs in the case of athletes [ 67 ]. All reflect various processes of neural plasticity, and it is striking that their sensitivity to sensory events happen a few milliseconds before the startle-eliciting stimulus.…”
Section: Prepulse Inhibition As An Indicator Of Neural Plasticitymentioning
confidence: 99%
“…Modifications of the PPI are very diverse and may be caused by neurological [48] or psychiatric diseases characterized by anxiety symptoms [49,50], behavioral states (as emotional context or a stressor) [51][52][53], hormonal levels [36,54,55], and even adaptations derived from particularities of some professions, as occurs in the case of athletes [56]. All reflect various processes of neural plasticity, and it is striking that their sensitivity to sensory events happen a few milliseconds before the startle-eliciting stimulus.…”
Section: Prepulse Inhibition As An Indicator Of Neural Plasticitymentioning
confidence: 99%